Tell me UCE: Gender violence in medical education. - Vargas, Ana (2021)
Objective: To make gender violence visible during medical training in the postgraduate program at the Universidad Central del Ecuador. Subjects and method: a mixed study was carried out among graduates and postgraduate students from 2012 to 2019 and university authorities. The virtual survey was addressed to 2,143 physicians and 358 responses were obtained; in-depth interviews were conducted with 13 postgraduates and 7 authorities. For the quantitative part, the frequencies of the variables were analyzed, as well as the association between them with the Chi2 test. The   qualitative analysis was made from the feminist theory and the gender approach. Results: 87% of the respondent’s report violence in the form of derogatory comments, sexual harassment and discrimination. The variables sex and perception of violence are independent. Regarding the qualitative part of the study, the discourses point to the symbolic weight of gender roles in training and professional practice, poor institutional response, lack of knowledge and lack of empowerment on the subject. Conclusions: In postgraduate medical training there is perception of gender violence, characterizing it contributes to quality assurance in higher education, allows guiding interventions to prevent it and helps to understand how it models professional practice in our country.